Capacity strengthening at ILRI—Graduate fellows and outreach (outputs to outcomes) - Mehta-Bhatt, Purvi (International Livestock Research Institute, 2011)
For the November 2011 'liveSTOCK Exchange' event at the International Livestock Research Institute (ILRI), Purvi Mehta, reflects on ILRI's capacity strengthening activities.